Filozofia religii Abrahama Joshuy Heschela - mistycyzm bez magii? - Pawlik, Andrzej (Studia Europaea Gnesnensia, 2016)
The article is devoted to the mystical nature of the philosophy of depth, as conceived Abraham Joshua Heschel. Although this philosophy draws strongly upon the Hasidic and Kabbalistic tradition, its mysticism is existential as opposed to magical.